Impact of the COVID‐19 pandemic on eating disorders diagnoses among adolescents and young adults in Catalonia: A population‐based cohort study. Issue 1 (9th November 2022) - Raventós, Berta; Abellan, Alicia; Pistillo, Andrea; Reyes, Carlen; Burn, Edward; Duarte‐Salles, Talita
Abstract: Objective: To describe the impact of the COVID‐19 pandemic on trends in incidence rates (IR) of diagnoses of eating disorders (ED) among adolescents and young adults. Methods: Population‐based cohort study using primary care records of people aged 10–24 years between January, 2016 and December, 2021 in Catalonia, Spain. IRs were calculated monthly and grouped by the different stages of the COVID‐19 pandemic in Catalonia: (1) the pre‐lockdown (January, 2016–February, 2020), (2) lockdown (March–June, 2020) and, (3) post‐lockdown (July, 2020–December, 2021) periods. Incidence rate ratios (IRR) relative to the corresponding periods in 2018–2019 were calculated. Results: A total of 1, 179, 009 individuals were included. The IR was 9.2 per 100, 000 person‐months (95% confidence intervals [CI]: 8.9–9.5) during the pre‐lockdown period. It decreased during the lockdown period (6.3 per 100, 000 person‐months [5.5–7.3]), but substantially increased during the following period (19.4. per 100, 000 person‐months [18.7–20.1]). While large reductions in IRs were observed for both sexes during the lockdown period (IRR 95% CI: 0.65 [0.54–0.78] in females and 0.46 [0.29–0.71] in males), substantial increases during the post‐lockdown period were limited to females, and were particularly pronounced among those aged 10–14 and 15–19 years (2.50 [2.23–2.80] and 2.29 [2.07–2.54], respectively). Discussion: The COVID‐19 pandemic has resulted in a substantial increase in ED diagnoses, primarily driven by higher rates among adolescent females. Public Significance: This population‐based cohort study demonstrated a substantial increase in incidence rates of eating disorders in primary care following the end of lockdown in Catalonia, Spain, with adolescent girls seen to be most affected.